Effect of Passage History on Dengue-2 Virus Replication in Subpopulations of Human Leukocytes - Brandt, Walter E. (1979)
Three passage levels of dengue-2 virus strain PR-159, obtained during the course of deriving the attenuated S-1 vaccine, were tested for their ability to replicate in subpopulations of human peripheral blood leukocytes: (i) 6th primary African green monkey kidney (PGMK) cell passage (parent virus); (ii) 19th PGMK cell passage of a small-plaque-forming clone derived from the parent virus (S-1 PGMK virus); and (iii) virus derived by four additional passages of the S-1 PGMK virus in diploid fetal rhesus lung cells (S-1 vaccine virus). Replication of these PR-159 viruses and another strain of dengue-2 virus adapted to Raji cells (16681-Raji virus) was measured in adherent and nonadherent mononuclear cells. All viruses except the S-1 PGMK virus replicated in monocytes. Occasional replication of the S-1 PGMK virus was associated with reversion to parent virus. The addition to the monocyte cultures of low concentrations of homologous dengue-2 antibody or non-neutralizing heterologous antibody increased the yield of the parent virus as much as 400-fold. This phenomenon of immune enhancement usually enabled the S-1 PGMK virus to replicate slowly in monocytes, but the progeny virus produced large plaques similar to the parent virus. Replication of the S-1 vaccine virus in cultured monocytes did not result in the appearance of large plaques. We could not recover S-1 vaccine virus from monocytes harvested from infected volunteers in the same manner that monocytes from natural human infections yield wild virus. The three passage levels of PR-159 virus were tested for replication in lymphocytes in comparison with the 16681-Raji virus. Only the 16681-Raji virus replicated in human lymphocytes cultured with or without enhancing antibody.